The Correlation Between Self-Efficacy and Resilience Among Final-Year Students Working on Their Final Assignment - Shinta Dewi Latifa Narzhammi Putri; Apriyani Puji Hastuti; Indari Indari (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
The increased academic demands faced by final-year students during the final assignment writing process have raised concerns about their psychological capacity, particularly self-efficacy and resilience. This study aims to analyze the correlation between self-efficacy and resilience among final-year nursing students at ITSK RS dr. Soepraoen in Malang. This study employed a quantitative correlational design with a cross-sectional approach. Data were collected using validated questionnaires, namely the General Self-Efficacy Scale (GSES) and the Resilience Questionnaire Test (RQ-Test), from 51 respondents using total sampling. The results indicated that the majority of respondents had low levels of self-efficacy and resilience. Statistical analysis using Spearman’s correlation test revealed a significant correlation between self-efficacy and resilience (p < 0.05) with a strong negative correlation coefficient (r = -0.814). This indicates that variations in self-efficacy scores are associated with variations in resilience levels among the respondents. However, because it used a cross-sectional design, this study cannot establish a causal correlation. The research findings should be interpreted with caution because this study did not directly measure other psychological factors such as stress or anxiety that may influence both variables. Therefore, the correlation found is likely influenced by other variables